Effectiveness of soaking in bilimbi (Averrhoa bilimbi) extract in the treatment of formalin-contaminated salted lencam fish (Lethrinidae) - Harianti Harianti; Meri Astuti; Ratnawati Ratnawati; Besse Firma Jamal (Universitas Negeri Yogyakarta, 2026)
The widespread use of formalin as an illegal preservative in fish products poses serious risks to public health, highlighting the urgency of developing safe and natural mitigation methods. This study investigates the effectiveness of soaking salted lencam fish (Lethrinidae) in bilimbi (Averrhoa bilimbi L.) extract to reduce formalin levels. The research was conducted from August to September 2022 in three traditional markets—Palattae, Laccibung, and Patimpeng—in Bone Regency, Indonesia, with laboratory analysis performed at the Fishery Product Quality Implementation Center. An experimental approach was used, involving samples obtained from six fish traders, of which two samples (A1 and B2) were identified as positive for formalin contamination. These samples were treated by soaking in 70% bilimbi extract for 30 minutes, and data were analyzed using a paired t-test with SPSS 16.0. The results showed a notable reduction in formalin levels, where sample A1 decreased from 9 mg/kg to 5.6 mg/kg and sample B2 from 9 mg/kg to 5.2 mg/kg, with an average reduction of approximately 62% (60% and 64%, respectively). These findings indicate that bilimbi extract is effective as a natural agent for reducing formalin contamination in salted fish products. In conclusion, soaking salted lencam fish in bilimbi extract provides a practical and safer alternative for improving food safety and protecting consumer health.